ENVIRONMENTAL RADIOLOGY AND QUALITY ASSURANCE FOR NPP SITE SELECTION - Susetyo Trijoko; Fepriadi Fepriadi (Jurnal Forum Nuklir, 2020)
ENVIRONMENTAL RADIOLOGY AND QUALITY ASSURANCE FOR NPP SITE SELECTION. This research briefly explains environmental radiology and quality assurance for NPP sites compiled from regulations, standard documents, and national and international literature. The selection of sites on the coast needs to be performed through research concerning local meteorological conditions with radioactive elements distributed to humans and the surrounding environment through the air and water body. Environmental radiology measurements and monitoring need to be programmed and implemented starting from the initial stage of site selection to the decommissioning. Quality assurance programs for sample measurements and environmental radiology have to be established to ensure the validity of measurement results and have to be reviewed and verified by independents which indirectly involved in measurement and research.